Effect of metabolic syndrome and thyroid hormone on efficacy of desvenlafaxine 50 and 100 mg/d in major depressive disorder. (3rd March 2016) - McIntyre, Roger S.; Fayyad, Rana; Mackell, Joan A.; Boucher, Matthieu
ABSTRACT: Objective This pooled, post hoc analysis evaluated the efficacy of desvenlafaxine vs placebo in adults with major depressive disorder (MDD) with and without metabolic syndrome, and above or at or below median baseline thyroid-stimulating hormone (TSH) levels. Research design and methods Patients were randomly assigned to receive desvenlafaxine 50 or 100 mg/d or placebo in nine short-term, double-blind studies. Metabolic syndrome was defined as meeting at least three of five criteria based on body mass index, triglycerides, high-density lipoprotein, fasting glucose, blood pressure, current medication, and medical history. Clinical trial registration NCT00072774; NCT00277823; NCT00300378; NCT00384033; NCT00798707; NCT00863798; NCT01121484; NCT00824291; NCT01432457 Main outcome measures Treatment effects on change from baseline in 17-item Hamilton Rating Scale for Depression (HAM-D17 ) total score at week 8 (last observation carried forward [LOCF]) were analyzed in four subgroups—metabolic syndrome and no metabolic syndrome, baseline TSH levels above median or at or below median—using analysis of covariance with treatment, study, and baseline in the model. Metabolic syndrome and TSH were examined as predictors of change in HAM-D17 total score using regression analysis. Results The pooled analysis included 4279 patients; 971 (22.7%) patients had metabolic syndrome. In all subgroups, HAM-D17 total scores improved significantly from baseline to week 8 (LOCF) with desvenlafaxine 50 or 100 mg/d compared with placebo (all p  ≤ 0.006). There was no significant treatment by metabolic syndrome or by TSH interaction. Neither metabolic syndrome nor TSH above median predicted change in HAM-D17 total scores, response (≥50% reduction in HAM-D17 total score), or remission (HAM-D17 total score ≤7; all p  > 0.05). Limitations Individual studies included in this analysis were not designed to examine the relationship between metabolic syndrome or TSH and response to desvenlafaxine treatment. Metabolic syndrome status was determined post hoc based on available baseline measures and not diagnosed at study entry. Exclusion criteria were selected to enroll medically healthy patients with a primary diagnosis of MDD (i.e., patients healthier than the general MDD population). Conclusions Desvenlafaxine 50 and 100 mg/d significantly improved depression compared with placebo in patients with and without metabolic syndrome, and in patients with baseline TSH above median and at or below median levels.